'n Ondersoek na die bereiking van die programdoelstellings van die vierjaar diplomakursus - M. P. Koen; L. de Villiers (AOSIS, 1996)
A descriptive survey was undertaken to determine the the extent to which the programme objectives for the Diploma in Nursing Leading to Registration as a Nurse (General, Psychiatric, Community) and Midwifery are being met. Questionnaires were completed by diplomates and nursing service managers. Various problem areas regarding realization of the programme objectives were identified.